The impact of manager’s experiences in entrepreneurship evidence from Kosovo SME’s - Esat DURGUTI; Enver Krasniqi; Dea Krasniqi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This research accords with a detailed overview of management in general regarding SME growth development in Kosovo. So, it deals with the main factors such as the main components of management and its impact on the success and development, the techniques, and the approaches to assess the SME economic system and their development. There is no unique model which explains the managing or manager's experience and firm growth in the complexion of management theories. We have also pointed out the life cycle phases of firms that are not constructed on economic theory but have received considerable attention from managerial theories of enterprises. So, chronologically was analyzed SME development in general, given that Kosovo has a liberal trade regime characterized by simplicity and neutrality of business or SME registration. In our data analysis, we applied Cronbach's alpha for reliability analysis and linear regression. The findings of the paper show that two main topics are management experience and the growth of the sector where they operate has a significant impact. The revision opens a challenge besides wide-ranging debate taking place entrepreneurship and supervision skills in Kosovo. However, this examination has to do with evidence in Kosovo and cannot be generalized to all countries. This investigation is one of the rare researches in this field in Kosovo, which deals with the topic of SME development. This treatment approach should be used by applying dynamic approaches as well as other factors.